Testing Lorentz invariance and CPT conservation with NuMI neutrinos in the MINOS near detector. - Adamson, P; Andreopoulos, C; Arms, K; Armstrong, R; Auty, D; Ayres, D; Baller, B; Barr, G; Barrett, W; Becker, B; Belias, A; Bernstein, R; et al. (2008)
A search for a sidereal modulation in the MINOS near detector neutrino data was performed. If present, this signature could be a consequence of Lorentz and CPT violation as predicted by the effective field theory called the standard-model extension. No evidence for a sidereal signal in the data set was found, implying that there is no significant change in neutrino propagation that depends on the direction of the neutrino beam in a sun-centered inertial frame. Upper limits on the magnitudes of the Lorentz and CPT violating terms in the standard-model extension lie between 10(-4) and 10(-2) of the maximum expected, assuming a suppression of these signatures by a factor of 10(-17).